David and Goliath : underdogs, misfits, and the art of battling giants - Gladwell, Malcolm, 1963- (Little, Brown and Company, 2013)
Malcolm Gladwell challenges how we think about obstacles and disadvantages, offering a new interpretation of what it means to be discriminated against, or cope with a disability, or lose a parent, or attend a mediocre school, or suffer from any number of other apparent setbacks. He begins with the real story of what happened between the giant and the shepherd boy (David and Goliath) those many years ago. From there, the book examines Northern Ireland's Troubles, the minds of cancer researchers and civil rights leaders, murder and the high costs of revenge, and the dynamics of successful and unsuccessful classrooms, all to demonstrate how much of what is beautiful and important in the world arises from what looks like suffering and adversity.